Penerapan E-Commerce Untuk Penyalur dan Jual Beli Hewan Qurban - Andika Bayu Shantya Budi; Galih Priambodo; Sony Wirdianto Saputra; Yudo Devianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Eid al-Adha is feast that is usually commorated by muslim, which is once a year. The need for qurban animals both for the needs of the eid al-adha holiday or needs orther than eid al- adha such as aqiqah, or orther important events are needed where in the selection of sacrificial animals such as goats or cows is very important both types of goats and sacrificed cattle, the condition of animals sacrificed so that the result given are very good. In the process of selecting, purchasing, distributing sacrificial animals still use manual methods so that it is less efficient so it needs the need for an application system that can help in making the selection, purchase and distribution of sacrificial animals. The method used is the waterfall method. This study aims to analyze the process of the selection,purchase and distribution of sacrificial animals to famers so that a solution to the problems of the process can be produced. In this research, the output produced is a web-based system application that can facilitate the purchase and distribution of sacrificial animals.